BUILDING DATA MARTS IN TEACHING MANAGEMENT: A CASE STUDY IN CENTER FOR HUMAN RESOURCE DEVELOPMENT: Received: 21st July 2022; Revised: 10th October 2022, 19th October 2022, 31st October 2022; Accepted: 8th November 2022 - Suprijandoko, Firman (PUPIL: International Journal of Teaching, Education and Learning, 2022)
This research is a series of researches with the theme Smart-Pusdiklat in the environment of State Cyber and Crypto Agency (BSSN). The locus chosen is the Human Resources Development Center (Pusbang) which is a subset of BSSN. Pusbang is a supporting element of the duties and functions of BSSN, which has the task of carrying out functional position coaching, and developing human resource competencies in the field of cyber security. The research question expressed is how to make leaders at Pusbang and stakeholders can make more comprehensive and fast decisions in managing institutions with the help of data warehouses. The researcher conducted a projection to build a data warehouse, which was then focused on becoming a specific data mart, and explained how users could access it for teaching management purposes at Pusbang. This research uses exploratory research methods with a qualitative approach. This method is intended to try a new phenomenon that may not have been before. This is the novelty value of this study. Researcher project the construction of 4 (four) data marts, namely JFKamsiber, References, Lecturer profiles, and Alumni data mart. Where this can make it easier for users to analyze, report and mine data in teaching management.